Robustly High Hippocampal BDNF levels under Acute Stress in Mice Lacking the Full-length p75 Neurotrophin Receptor - Schott, Björn H.; Kronenberg, Golo; Schmidt, Ulrike; Düsedau, Henning P.; Ehrentraut, Stefanie; Geisel, Olga; von Bohlen und Halbach, Oliver; Gass, Peter; Dunay, Ildiko Rita; Hellweg, Rainer (Pharmacopsychiatry, 2021)
Background Brain-derived neurotrophic factor (BDNF) exerts its effects on neural plasticity via 2 distinct receptor types, the tyrosine kinase TrkB and the p75 neurotrophin receptor (p75NTR). The latter can promote inflammation and cell death while TrkB is critically involved in plasticity and memory, particularly in the hippocampus. Acute and chronic stress have been associated with suppression of hippocampal BDNF expression and impaired hippocampal plasticity. We hypothesized that p75NTR might be involved in the hippocampal stress response, in particular in stress-induced BDNF suppression, which might be accompanied by increased neuroinflammation.Method We assessed hippocampal BDNF protein concentrations in wild-type mice compared that in mice lacking the long form of the p75NTR (p75NTRExIII−/−) with or without prior exposure to a 1-hour restraint stress challenge. Hippocampal BDNF concentrations were measured using an optimized ELISA. Furthermore, whole-brain mRNA expression of pro-inflammatory interleukin-6 (Il6) was assessed with RT-PCR.Results Deletion of full-length p75NTR was associated with higher hippocampal BDNF protein concentration in the stress condition, suggesting persistently high hippocampal BDNF levels in p75NTR-deficient mice, even under stress. Stress elicited increased whole-brain Il6 mRNA expression irrespective of genotype; however, p75NTRExIII−/− mice showed elevated baseline Il6 expression and thus a lower relative increase.Conclusions Our results provide evidence for a role of p75NTR signaling in the regulation of hippocampal BDNF levels, particularly under stress. Furthermore, p75NTR signaling modulates baseline but not stress-related Il6 gene expression in mice. Our findings implicate p75NTR signaling as a potential pathomechanism in BDNF-dependent modulation of risk for neuropsychiatric disorders.
Keywords: brain-derived neurotrophic factor; BDNF; interleukin 6; IL-6; p75NTR; stress; hippocampus